Masticatory Adaptation to Occlusal Changes - Bourdiol, Pierre; Hennequin, Martine; Peyron, Marie-Agnes; Woda, Alain (Frontiers in Physiology, 2020)
This review deals with the frequent wide variability of masticatory capacity/incapacity. Neither researchers nor clinicians have taken sufficient account of this variability despite its implications for nutrition. Mastication in normal healthy oral conditions is first described, followed by a short presentation of the mechanisms of masticatory adaptation in the nervous system. Capacity, incapacity, and successful compensatory adaptation of mastication are then defined, along with the different methods used for their evaluation. Examples of adaptation needs are given, such as those concomitant with dental wear or occlusal changes. Finally, given its vital importance for deeply impaired mastication/deglutition function, the impact of masticatory adaptation processes on nutrition is examined.